Metformin Induces PRODH/POX-Dependent Apoptosis in Breast Cancer Cells - Huynh, Thi Yen Ly; Oscilowska, Ilona; Szoka, Lukasz; Piktel, Ewelina; Baszanowska, Weronika; Bielawska, Katarzyna; Bucki, Robert; Miltyk, Wojciech; Palka, Jerzy (Frontiers in Molecular Biosciences, 2022)
Although the antineoplastic activity of metformin (MET) is well established, the underlying mechanism is not understood. One of the effects of MET is activation of AMP kinase (AMPK). Since proline dehydrogenase/proline oxidase (PRODH/POX) is activated by AMPK ligands (implicated in regulation of cancer cell survival/apoptosis), the effect of MET on PRODH/POX-dependent apoptosis in wild type MCF-7 cells (MCF-7WT) and POX knockdown MCF-7 cells (MCF-7crPOX cells) was studied. PRODH/POX catalyzes proline degradation generating ROS-induced apoptosis or autophagy. Proline availability for PRODH/POX is regulated by prolidase activity (proline supporting enzyme), collagen biosynthesis (proline utilizing process) and interconversion of proline, glutamate and ornithine. We have found that MET is cytotoxic for MCF-7 cells (IC50 17 mM), and to the lower extent for MCF-7crPOX cells (IC50 28 mM). In MCF-7WT cells the effect was accompanied by inhibition of DNA and collagen biosynthesis, increase in ROS formation, AMPKα phosphorylation, and expression of prolidase, p53, caspase 8, caspase 9 and cleaved PARP. In MET-treated MCF-7crPOX cells the processes were less affected than in MCF-7WT cells, expression of caspase 9 was decreased, while cleaved caspase 8 as well as cleaved PARP were not detected. The effects were accompanied by increase in prolidase activity and intracellular proline concentration. The mechanism for MET-induced apoptosis involves up-regulation of prolidase activity and decrease in collagen biosynthesis in effect providing substrate (proline) for PRODH/POX-dependent ROS formation and activation of caspases- 9 and -8. The data suggest that PRODH/POX participate in the MET-induced intrinsic and extrinsic apoptosis in MCF-7 cells.